Magnetohydrodynamic blood flow in patients with coronary artery disease. (September 2018) - Javadzadegan, Ashkan; Moshfegh, Abouzar; Afrouzi, Hamid Hassanzadeh; Omidi, Mohammad
Highlights: Effect of a magnetic field with varying intensities on haemodynamic perturbations in a cohort of 25 patients with coronary artery disease was studied. Transient computational fluid dynamics simulations were performed in three-dimensional models of coronary arteries reconstructed from three-dimensional quantitative coronary angiography. In the presence of magnetic field, substantial reductions were observed in shear stress over stenosis segment, size of regions with low shear stress and length of flow recirculation zones, in particular for coronaries with moderate to severe stenoses. In contrast with stenosis segment, the presence of a magnetic field led to a considerable increase in shear stress in the pre-stenotic segment, in particular in coronary arteries with mild lesions. An externally applied magnetic field can improve haemodynamic perturbations in human coronary arteries. The value of implementing an external magnetic field to reduce haemodynamic perturbations and therefore preventing atherosclerosis progression warrants further investigation. Abstract: Objectives: We aim to investigate the effect of a magnetic field with varying intensities on haemodynamic perturbations in a cohort of patients with coronary artery disease. Methods: Transient computational fluid dynamics (CFD) simulations were performed in three-dimensional (3D) models of coronary arteries reconstructed from 3D quantitative coronary angiography. The effect of magnetic field on wall shear stress (WSS) derived parameters including maximum wall shear stress (MWSS) and size of regions with low wall shear stress (ALWSS) as well as length of flow recirculation zones were determined. Results: The results showed a substantial reduction in MWSS, ALWSS and length of flow recirculation zones in the presence of magnetic field, in particular for coronaries with moderate to severe stenoses. When the whole cohort examined, time-averaged wall shear stress (TAWSS), ALWSS and the length of flow recirculation zones in the absence of magnetic field were approximately 1.71, 4.69 and 8.46 times greater than those in the presence of magnetic field, respectively. Conclusion: Our findings imply that an externally applied magnetic field can improve haemodynamic perturbations in human coronary arteries.